ANALISIS KADAR SENYAWA FLAVONOID DARI EKSTRAK ETANOL DAUN KAKAO (Theobroma cacao L.) DENGAN PERBANDINGAN DAERAH TEMPAT TUMBUH - Mahmud, Nurul Faiza; Maryam, St; Suhaenah, Asriani (PHARMACY UMI JOURNAL SYSTEM, 2024)
Cocoa leaves (Theobroma cacao L.) contain active compounds that have many health benefits. Flavonoids are one of the active compounds contained therein that can prevent the formation of free radicals and reduce tissue damage due to inflammation. This study aims to determine the flavonoid content of ethanol extract of cacao leaves (Theobroma cacao L.) based on the comparison of growing regions using the UV-Vis spectophotometric method. Samples were taken from three regions namely Jeneponto, Wajo and Malino. This research method begins with the preparation of samples by maceration with 96% ethanol solvent, then qualitative analysis is carried out by Thin Layer Chromatography (KLT) method and quantitative analysis is carried out measuring quercetin standards and determining flavonoid levels with a UV-Vis spectrophotometer at a maximum wavelength of 430 nm. The results showed that the ethanol extract of cocoa leaves (Theobroma cacao L.) positively contained flavonoids and had flavonoid levels in the Jeneponto, Wajo, Malino regions of 45.812 mgQE/g extract; 41.556 mgQE/g extract, and; 38.343 mgQE/g extract, respectively. Where the ethanol extract of cocoa leaves (Theobroma cacao L.) from the Jeneponto region has higher flavonoid levels than the other two regions.